Kemahiran ICT di kalangan guru pelatih IPTA Malaysia - Abu Bakar, Zainuddin (Faculty of Education, 2007)
Information Communication and Technology becomes phenomenon to our lives today. We cannot escape of using technology. Nevertheless the development of technology has improved our quality of life. In education, a rapid change in utilising the ICT becomes materialised. In most part, teaching and learning, teaching aids, and assessment, to name some of it, has improved a lot because of ICT. Teachers are no longer planning their lesson without considering ICT. Assessment procedure has also bound by this development. Teaching personnel, teachers in specific, are requires of being competence not just of their subject but the ICT as well. Most of the planning process requires ICT to be considered. The use of LCD projector, power point presentation, laptop, specific courseware and software requires teacher to go one level up in order to function effectively. The Ministry of Education in this sense was positively embarked on the ICT competency among teachers. As a result the teaching profession become crucial to have a teacher with not only their subject but ICT competencies. It has been started way back during their training programme. One of the important elements in the teacher training programme is the integration of ICT to teaching and learning processes. The trainees are expected to acquire sufficient skills related to ICT. This study is therefore focuses on the ICT competency among trainee teachers in the Malaysian Public Universities. In specific, the study explores the trainees' ICT competencies before being placed in their actual school. 2303 respondents across the 11 public universities were involved in the study. They were students who are in their final year of the programme. Questionnaire was used to collect the data, The analysis of mean and percentage has been executed to answer the research questions. It was found the level of ICT competency among respondents is varied across universities. It shows that according to the types of courses (mathematics and science, technical and engineering, and social science) the degree of competencies was also varied. However, in general the findings showed that majority of the trainees are competence in ICT. One of the identified problems regarding the development of the ICT competency is the accessibility of the facility. Some of universities, regardless their courses have some difficulties of providing enough computers and other related materials to their student. An ICT Competency Model was proposed. Further recommendation and suggestions are also discussed.